IL-5Rα marks nasal polyp IgG4- and IgE-expressing cells in aspirin-exacerbated respiratory disease - Buchheit, Kathleen M.; Dwyer, Daniel F.; Ordovas-Montanes, Jose; Katz, Howard R.; Lewis, Erin; Vukovic, Marko; Lai, Juying; Bankova, Lora G.; Bhattacharyya, Neil; Shalek, Alex K.; Barrett, Nora A.; Boyce, Joshua A.; et al. (Journal of allergy and clinical immunology, 2020)
The cause of severe nasal polyposis in aspirin-exacerbated respiratory disease (AERD) is unknown. Elevated antibody levels have been associated with disease severity in nasal polyps, but upstream drivers of local antibody production in nasal polyps are undetermined. We sought to identify upstream drivers and phenotypic properties of local antibody-expressing cells in nasal polyps from subjects with AERD. Sinus tissue was obtained from subjects with AERD, chronic rhinosinusitis (CRS) with nasal polyps (CRSwNP), CRS without nasal polyps, and controls without CRS. Tissue antibody levels were quantified via ELISA and immunohistochemistry and were correlated with disease severity. Antibody-expressing cells were profiled with single-cell RNA sequencing, flow cytometry, and immunofluorescence, with IL-5Rα function determined through IL-5 stimulation and subsequent RNA sequencing and quantitative PCR. Tissue IgE and IgG4 levels were elevated in AERD compared with in controls (P < .01 for IgE and P < .001 for IgG4 vs CRSwNP). Subjects with AERD whose nasal polyps recurred rapidly had higher IgE levels than did subjects with AERD, with slower regrowth (P = .005). Single-cell RNA sequencing revealed increased IL5RA, IGHG4, and IGHE in antibody-expressing cells from patients with AERD compared with antibody-expressing cells from patients with CRSwNP. There were more IL-5Rα+ plasma cells in the polyp tissue from those with AERD than in polyp tissue from those with CRSwNP (P = .026). IL-5 stimulation of plasma cells in vitro induced changes in a distinct set of transcripts. Our study identifies an increase in antibody-expressing cells in AERD defined by transcript enrichment of IL5RA and IGHG4 or IGHE, with confirmed surface expression of IL-5Rα and functional IL-5 signaling. Tissue IgE and IgG4 levels are elevated in AERD, and higher IgE levels are associated with faster nasal polyp regrowth. Our findings suggest a role for IL-5Rα+ antibody-expressing cells in facilitating local antibody production and severe nasal polyps in AERD.